2000
DOI: 10.1038/labinvest.3780099
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Placental Site Trophoblastic Tumor May Require the Presence of a Paternally Derived X Chromosome

Abstract: SUMMARY:Placental site trophoblastic tumor (PSTT) is a neoplastic proliferation of intermediate trophoblasts that invades the myometrium at the placental site after a pregnancy. Less than 100 cases have been reported. Information of the sex assignment of the antecedent gestation is available in 21 cases: 18 of these were female. To explore this interesting phenomenon, we have determined the sex chromosome composition of the tumor tissue preserved in paraffin blocks for five new cases of this condition. The las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…6,7 We have previously noted through literature reviews that a majority of the tumors were preceded by a female gestational event and our pilot molecular investigation suggested that the tumorigenesis likely requires the presence of a paternally derived X chromosome in the tumor genome. 8 We now present an analysis of a larger series of cases to confirm these earlier observations.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…6,7 We have previously noted through literature reviews that a majority of the tumors were preceded by a female gestational event and our pilot molecular investigation suggested that the tumorigenesis likely requires the presence of a paternally derived X chromosome in the tumor genome. 8 We now present an analysis of a larger series of cases to confirm these earlier observations.…”
supporting
confidence: 69%
“…8 Since then, additional case reports of placental site trophoblastic tumor have been published and again a female antecedent pregnancy was documented in 12 out of 14 new cases. [13][14][15] One cell line from a placental site trophoblastic tumor was established and confirmed by karyotyping to have XX genome.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of hybridization signal to a small number of Y-chromosomes likely represents a nonspecific finding, which has been observed a similar study 7 and our previous study using nested genomic PCR failed to demonstrate Y-chromosome-specific sequences in tumour cells of these cases. 4 Histologically, the two tumours with abnormal CGH output (cases 1 and 2) showed no significant morphological differences from the other two tumours having a balanced CGH profile (cases 3 and 4). Clinical follow-up information was available in two patients (cases 2 and 4) who were alive without evidence of tumour recurrence.…”
Section: Resultsmentioning
confidence: 99%
“…Although our understanding of the pathogenesis of GTDs is limited, an emerging body of data has suggested that abnormal genomic composition and altered epigenic regulation by genomic imprinting appear to play important roles in the development of GTDs. 4,[8][9][10] It is interesting that, comparable with the proliferative spectrum of GTDs, chromosomal alterations detectable by CGH increase as the lesion becomes more proliferative and aggressive. At the benign end, hydatidiform moles display balanced CGH profiles 11 and they carry the least proliferative potential, compatible with a non-neoplastic process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation